2007
DOI: 10.1645/ge-819r2.1
|View full text |Cite
|
Sign up to set email alerts
|

Epifaunistic Arthropod Parasites of the Four-Striped Mouse, Rhabdomys Pumilio, in the Western Cape Province, South Africa

Abstract: Flea, lice, mite, and tick species associated with 510 Rhabdomys pumilio were collected at 9 localities in the Western Cape Province, South Africa. The aims of the study were first to quantify the species richness, prevalence, and relative mean intensity of infestation of epifaunistic arthropod species associated with R. pumilio, and second to determine temporal variations in the mean abundance of the parasitic arthropods. Each mouse was examined under a stereoscopic microscope and its parasites were removed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
88
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(105 citation statements)
references
References 34 publications
(42 reference statements)
15
88
2
Order By: Relevance
“…Increases in mite abundance with rainfall have previously been reported for several other mite species in South Africa irrespective of whether rainfall occurs during winter (Matthee et al 2007;Archer et al 2014) or summer (Viljoen et al 2011) as in the current study. Unlike R. warburtoni/arnoldi the abundance of Ixodes spp.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Increases in mite abundance with rainfall have previously been reported for several other mite species in South Africa irrespective of whether rainfall occurs during winter (Matthee et al 2007;Archer et al 2014) or summer (Viljoen et al 2011) as in the current study. Unlike R. warburtoni/arnoldi the abundance of Ixodes spp.…”
Section: Discussionsupporting
confidence: 80%
“…infest murid rodents and sengis are hence only accidental hosts which may account for their low prevalence and abundance in the current study (Horak et al 2005;Matthee et al 2007;Apanaskevich et al 2007). …”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Such aggregation could have implications for the sex ratio of ectoparasite species due to the isolation of infrapopulations on individual hosts (Marshall, 1981;Poulin, 2007). The increasing isolation of such infrapopulations with decreasing ectoparasite prevalence and a resulting increased risk of inbreeding has been invoked to explain the commonly observed female bias of ectoparasites (Marshall, 1981;Matthee et al, 2007;Krasnov, 2008). In such populations, only a small number of males are required to fertilize all females, and females exhibit female-biased offspring sex ratios, resulting in reduced local mate competition (Hamilton, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Ectoparasites that have developmental stages that live off the host are thought to be particularly susceptible to effects associated with the surrounding habitat (Vinarski et al, 2007;Krasnov, 2008). However, no taxon-specific pattern is apparent, and although some studies have shown that lower levels of humidity can reduce the abundances (Krasnov, 2008;Viljoen et al, 2011), others have found the opposite pattern (Fabiyi, 1996;Matthee et al, 2007).…”
mentioning
confidence: 99%